The Interaction between Endophytic Actinomycetes and Rhizobium in Leguminous Plants - Sahur, Asmiaty (Journal of Tropical Crop Science, 2015)
Biological N2 fixation represents the major source of N input in many agricultural soils including those in arid regions where little artificial fertilizer is applied. The major N2-fixing systems in agriculture are the symbiotic systems, where bacteria such as rhizobia interact with legumes to fix atmospheric nitrogen which plays a significant role in improving the fertility and productivity of low-N soils. The symbiotic association of legume-rhizobium is initiated by the colonization of the rhizosphere by the rhizobia and subsequent attachment to the root hairs of the host plant. Furthermore, the host will produce flavonoids, such as luteolin in alfalfa and diazedin in soybean, which interact with nod protein in the rhizobia. Moreover, this process then elicits the expression of a cluster of nodulation genes such as nod, nol, and noe in the rhizobia. The interaction is potentially of great importance to the health and growth in nature of this nodulating legume.The interaction between endophytic Actinomycetes and rhizobia in leguminous plants is one way to improve the capability of leguminous plants to fix atmospheric nitrogen in plant roots and contribute to the plants nutrition. From other studies, we know that certain types of Actinomycetes, for example Streptomyces, interact with peas to form healthy roots as an effective site to form nodules and improve biological nitrogen fixation.  Knowledge about this activity against fungal pathogens might lead to finding biocontrol agents for use in sustainable agricultural practices.Root-colonizing soil borne Actinomycetes might influence root nodulation in leguminous plants by increasing root nodulation frequency, possibly at the sites of infection by Rhizobium spp.  Actinomycetes also colonize and sporulate within the surface cell layers of the nodules. This colonization leads to an increase in the average size of the nodules that form and improves the vigor of the bacteroids which generate the red color within the nodules by enhancing nodular assimilation of iron and possibly other soil nutrients. Keywords: symbiotic, biological, nitrogen, molecular interaction